Предмет: Алгебра, автор: olyabelyavskayakoval

1.Упростить выражения:

Приложения:

Ответы

Автор ответа: RayMiller
1

Объяснение:

5(а^6)*(–3а²b)²= 5(a^6)*9a⁴b²= 45(a^10)b²

{( -  {x}^{4}  {y}^{3} ) }^{7}  \times 8 {x}^{2}  {y}^{5}  =  -  {x}^{28}  {y}^{21}  \times 8 {x}^{2}  {y}^{5}  =  - 8 {x}^{30}  {y}^{26}

{( - 0.1 {a}^{2} b{c}^{5} ) }^{2}  \times 100b{c }^{4}  = 0.01 {a}^{4}  {b}^{2}  {c}^{ 10}  \times 100b{c}^{4}  =  {a}^{4}  {b}^{3}  {c}^{14}

 - 1 \frac{3}{5}  {m}^{4}  {n}^{3}  \times {( -  \frac{1}{2}  {m}^{3}  {p}^{6} ) }^{3}  = - \frac{8}{5}  {m}^{4}  {n}^{3}  \times  -  \frac{1}{8}  {m}^{9} {p}^{18}   =  \frac{1}{5}  {m}^{13}  {n}^{3}  {p}^{18}

2 \frac{1}{4}  {a}^{5} b \times {( \frac{2}{3} a {b}^{3} ) }^{3}  =  \frac{9}{4}  {a}^{5} b \times \frac{8}{27}  {a}^{3}{b}^{9}  =  \frac{2}{3}  {a}^{8}  {b}^{10}

 {( - 5 {a}^{3} {b}^{7}  )}^{3}  \times  {( -  \frac{1}{2}  {a}^{2}  {c}^{6} )}^{2}  =  - 125 {a}^{9}  {b}^{21}  \times  \frac{1}{4}  {a}^{4}  {c}^{12}  =  -  \frac{125}{4} {a}^{13}   {b}^{21}  {c}^{12}  =  - 31.25{a}^{13}   {b}^{21}  {c}^{12}.

Похожие вопросы
Предмет: Другие предметы, автор: иван543